PENERAPAN STRATEGI ONE MINUTE MIRROR UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN ILMU PENGETAHAUAN ALAM DI KELAS V SEKOLAH DASAR NEGERI 017 RANAH SINGKUANG - Desy susanti; Utia Virli Susanti (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2023)
The application of the One Minute Mirror strategy to improve student learning outcomes is the main objective of this research. This research is a classroom action research (CAR) which was motivated by the low learning outcomes of students in science class V. The subjects of this research were teachers and students of class V in the 2012-2013 academic year as many as 12 boys and 14 girls, so a total of 26 students. On the other hand, the aim of this research is to implement a one minute mirror strategy to improve students' science learning outcomes. Data collection techniques for this study using observation and test techniques. Before the action, 13 students completed the action or achieved 50.00% completeness, but in cycle I it increased to 18 students or reached 69.23% completeness. After corrective action was taken, Cycle II found that the completeness of students reached 24 students or the completeness of students reached 92.31%. This means that student learning outcomes have reached 75% of the specified KKM or 75. It can be concluded that the application of the One Minute Mirror strategy improves science learning outcomes for fifth grade students of SD 017 Ranah Singkuang, Kampar District, Kampar Regency.